SUSTAINABILITY IN INFORMATION SYSTEMS AUDITING - Alifah Aida Binti Lope Abdul Rahman; A. Al-Nemrat; D.S. Preston (European Scientific Journal, ESJ, 2014)
Auditing is a systematic process of obtaining and evaluating evidence of activities, events or transactions. Currently, audit practices have been revolutionized by the development of information technology and basically information systems auditing focuses on assessing proper implementation, operation and control of information systems resources within organisation. Several frameworks have been formulated for information systems auditing implementation to achieve improvement in auditing performance related to compliance requirements, internal controls evaluation and information systems success. However, sustainability dimensions in the information systems auditing practices and the development of appropriate framework are not enough discussed in the literature although sustainability is becoming significant in achieving certain organisation‘s objective. Therefore, this study intends to analyse the relevant requirements by auditors and sustainability factors and use them to formulate IS audit by integrating sustainability in the auditing process. Thus, improve audit performance and enhanced accountability and integrity of auditors.